2015
DOI: 10.1007/s11655-015-1965-0
|View full text |Cite
|
Sign up to set email alerts
|

Combination of total Astragalus extract and total Panax notoginseng saponins strengthened the protective effects on brain damage through improving energy metabolism and inhibiting apoptosis after cerebral ischemia-reperfusion in mice

Abstract: The combination of TAE 110 mg/kg and TPNS 115 mg/kg could strengthen protective effects on cerebral ischemia injury, the mechanism underlying might be related to improving jointly the early energy metabolism, and relieving the delayed apoptosis via inhibiting the mitochondrial apoptosis pathway of JNK signal transduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…The energy‐rich phosphate compound synthesis was significantly reduced after cerebral ischemia. Astragalus extract, AS‐IV (20–40 mg/kg, 3–7 day) alone or in combination with tetramethylpyrazine, could reverse the decreased glucose metabolism, increase the ATP and ADP level, the Na+‐K+‐ATPase activity, and the EC value, and improve the energy synthesis and supply to attenuate cerebral ischemia damage .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy‐rich phosphate compound synthesis was significantly reduced after cerebral ischemia. Astragalus extract, AS‐IV (20–40 mg/kg, 3–7 day) alone or in combination with tetramethylpyrazine, could reverse the decreased glucose metabolism, increase the ATP and ADP level, the Na+‐K+‐ATPase activity, and the EC value, and improve the energy synthesis and supply to attenuate cerebral ischemia damage .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 99%
“…AS‐IV downregulated TNF‐α, IL‐1β, and other inflammatory cytokine expression by inhibiting the activation of NF‐κB signaling pathway via attenuating the phosphorylation of I κ B and decreasing the nuclear translocation of NF‐κB. The total astragalus extract also could decrease the apoptosis rate through the of JNK signaling transduction by downregulate the expression of p‐JNK1/2, Cyt‐C, caspase‐9, and caspase‐3 . Suppression of neutrophils’ adhesion‐related molecules. Neutrophils are acknowledged to be pivotal in inflammatory response, so it became a new approach to exert neuroprotection by suppression of neutrophil infiltration and activation after CIRI .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 99%
“…Astragaloside IV (AS‐IV), an important derivative of A. membranaceus , could alleviate airway inflammation when it was applicated early in asthma. AS‐IV is able to inhibit the inflammatory response and provide the protective effect on the respiratory system (Brouns & De Deyn, ; Huang, Tan, Chen, & Deng, ; Jin, Yang, & Li, ). Besides, some studies showed AS‐IV attenuates the eosinophilic infiltration in ovalbumin‐induced asthma (Du et al, ; Gu, Jiang, Wang, Du, & Cai, ; Huang, Tang, Wang, & Song, ).…”
Section: Discussionmentioning
confidence: 99%
“…# p < 0.05 and ## p < 0.01 compared with control group; *p < 0.05 and **p < 0.01 compared with OVA group [Colour figure can be viewed at wileyonlinelibrary.com] could alleviate airway inflammation when it was applicated early in asthma. AS-IV is able to inhibit the inflammatory response and provide the protective effect on the respiratory system (Brouns & De Deyn, 2009;Huang, Tan, Chen, & Deng, 2017;Jin, Yang, & Li, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data show that PNS and its constituents have anti-inflammatory [10, 11], anti-oxidant [12, 13], and anti-apoptotic properties [13, 14] in both global and focal ischemic cerebrovascular disease. However, it is not clear whether PNS have a protective impact on the restoration of microvascular dyshomeostasis, which is essential to tissue survival after I/R.…”
Section: Introductionmentioning
confidence: 99%